ChemInform Abstract: Stereoselective Intermolecular Nitroaminoxylation of Terminal Aromatic Alkynes: Trapping Alkenyl Radicals by TEMPO. Issue 22 (15th May 2015) - Yan, Hong; Rong, Guangwei; Liu, Defu; Zheng, Yang; Chen, Jie; Mao, Jincheng
Abstract: Terminal aryl and hetarylalkynes are transformed in high yields, whereas alkylalkynes furnish the corresponding products in significantly lower yields.